2018
DOI: 10.1111/jan.13848
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing paternal involvement during infancy: A prospective longitudinal study

Abstract: Fathers (first-time and experienced) who were involved during their infant's birth were also involved at 6-month postpartum. Healthcare professionals may encourage paternal involvement through teaching fathers infant care skills during the antenatal period, especially first-time fathers as they may be lacking in such skills, which may hinder their parenting satisfaction. Paternal involvement throughout the perinatal period can be enforced by healthcare professionals to promote paternal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
1
14
0
2
Order By: Relevance
“…A recent study by Shorey et al [117] found that high paternal self-efficacy is one of the main factors of high paternal involvement during infancy, especially among first-time fathers. Higher paternal self-efficacy also leads to increase in parenting satisfaction over the first 6 months postpartum [118]. According to a review on informational interventions aiming to improve paternal outcomes [117], there were only three interventions (via online dissemination of information or self-modelled videotaped interaction and feedback) that reported on paternal self-efficacy [119][120][121], but only Hudson et al's [119] study found an intervention effect on parenting self-efficacy and parenting satisfaction in fathers.…”
Section: Role Of Self-efficacy In Parental Outcomes In the Perinatal mentioning
confidence: 99%
“…A recent study by Shorey et al [117] found that high paternal self-efficacy is one of the main factors of high paternal involvement during infancy, especially among first-time fathers. Higher paternal self-efficacy also leads to increase in parenting satisfaction over the first 6 months postpartum [118]. According to a review on informational interventions aiming to improve paternal outcomes [117], there were only three interventions (via online dissemination of information or self-modelled videotaped interaction and feedback) that reported on paternal self-efficacy [119][120][121], but only Hudson et al's [119] study found an intervention effect on parenting self-efficacy and parenting satisfaction in fathers.…”
Section: Role Of Self-efficacy In Parental Outcomes In the Perinatal mentioning
confidence: 99%
“…Taken these together, a minimally adequate sample size for this study would be at least 178. Based on the previous studies among Singaporean parents (Shorey et al, 2014(Shorey et al, , 2019(Shorey et al, , 2015b 15% of attrition rate was considered in this study. Hence, a total of 205 [(178 + 27 (15% of 178) = 205] parents were needed for this study.…”
Section: Participantsmentioning
confidence: 99%
“…All the instruments used in this study including Parenting Efficacy Scale, Perceived Social Support for Parenting Scale, EPDS and "What Being the Parent of a New Baby is like" were validated among local parents in the previous studies (Shorey et al, 2014(Shorey et al, , 2019.…”
Section: Validity Reliability and Rigormentioning
confidence: 99%
“…Una de las limitaciones del estudio es el tamaño y la procedencia homogénea de la muestra (contexto de pobreza), lo cual exige, para futuros estudios, trabajar con muestras que tengan mayor representatividad estadística y de diferentes niveles socioeconómicos y educativos. Así mismo, para investigar sobre los procesos co-regulatorios de los bebés, sería recomendable utilizar el enfoque sistémico de la familia (Feldman, 2012), ya que permite explorar el papel que juega el padre y otras figuras familiares cercanas en dichos procesos, si se considera que en los contextos familiares de cuidado infantil contemporáneos, no solo la madre juega un rol central en la crianza de los niños pequeños, sino también otras figuras familiares, como el padre, que en las últimas décadas ha mostrado involucramiento en la crianza y cuidado temprano cada vez mayor Shorey, Ang, Goh, & Gandhi, 2019).…”
Section: Limitaciones Y Proyecciones Del Estudiounclassified